The Influence of Service Quality and Brand Reputation on Customer Satisfaction in Zakat Institution - Sany Sanuri Mohd Mokhtar; Salniza Md Salleh; Hasnizam Shaari; Siti Noratisah Mohd Nafi (International Journal of Supply Chain Management, 2020)
Zakat services are one of the vital things that being emphasized in Islam, however, there is often a dispute between givers and zakat recipients over the quality of their services in handling the zakat. The problem is more critical when it involved the quality of services provided by the institution that has been appointed by the government in delivering the zakat. Amongst the components that have been stressed by the customers are the service quality and reputations of the zakat Institution. This study aimed to explore the effects of service quality and reputation towards the customers’ satisfaction at one of the Zakat Institutions in one of the state in Malaysia. Respondents for this study were residences who reside in the state and used the Institution services. There were 280 questionnaires have been distributed to the respondents. The study found that reliability, assurance and brand reputation does have significant relationship towards the customers’ satisfaction.